Marketing in Politics: Case of Congress and Bharatiya Janata Party - Begde, Prasad (Indian Journal of Marketing, 2011)
After winning the central election in 2009, Congress got majority in three states. This paper briefly describes the well designed STP approach in marketing used by the congress party. The paper will also describe the Image building, Youth factor, Promotion and product design of congress party by the Gandhi Family. Rahul Gandhi's political goals (right, left or center) don't really change the reality that marketing in politics is changing forever. The idea of a youth factor and "near to everyone approach". Bharatiya Janta Party (BJP) used its online campaign 'Bloggers for Advani' and SMS. They earlier launched a blog and massive online advertising campaign to create awareness about the Prime Minister Candidate. Such skepticism on the importance of the internet in Indian politics has valid reasons, given that less than 5% of Indians have internet access. The article also portrays BJP's previous promotion campaign "Feel Good" and "India Shining" of BJP used in 2004's election. But the campaign flopped because of opposition attack and used India's reality -Poverty, unemployment etc. The article also compares BJP and Congress party on their communication campaigns.